KAJIAN PERBAIKAN PATAHAN PADA RUNWAY - Bolla, Margareth E.; Cornelis, Remigildus; Amtiran, Jelmi Y. (Jurnal Teknik Sipil, 2013)
At the runway pavement of El Tari Kupang Airport, there was damage in the form of fracture that occurred at the edge of the pavement, which could disrupt aircraft traffic line. Due to the problem, the purposes of this research are to find out the cause of fracture, and to assess the reconstruction of the runway pavement that has been done by PT Angkasa Pura, Kupang. As the research conducted, it was found out that the cause of the fracture was more prevalent due to the lack of drainage system of the Airport. The slope of the runway shoulder was only 1.60% - 1.80%, was improper to the FAA minimum standard of slope that was 2.50% - 5.00%, and the unavailability of inlet pipes for subsurface drainage. The result of reconstruction done by PT Angkasa Pura has fulfilled the FAA standard. The total thickness of the reconstruction is 52.00 cm, is compliant with the minimum thickness of FAA standard 50.07 cm. However, the reconstruction of the pavement would be for short term solution only because of the poor drainage system of El Tari Kupang Airport has not been handled properly.